An Analysis on the Language Style of the Utterances in Magnum Advertisements - Permatasari, Sonia Niken; Yulia, Made Frida (LLT Journal: A Journal on Language and Language Teaching, 2013)
The role of broadcasted advertisements is undeniably important for the companies to market their products. To convince the audience, advertisers have to convey the persuasive message through the use of linguistic features. Those linguistic features will influence the persuasion techniques used in advertisements and the power relation which is built between the companies and the consumers. This study attempted to s olve two research problems related to the language style of the utterances in Magnum advertisements. They were (1) What are the linguistic features of Magnum advertisements? (2) What kind of power relation does Magnum have upon consumers through the advertisements As an endeavor to solve those two problems, document analysis was employed in analyzing the transcript of the utterances in ten (10) Magnum advertisements. The first research problem was solved by categorizing the words or the sentences into some linguistic features of advertising language proposed by Grey (2008). The second research problem was solved by interpreting the power relation in Magnum advertisements based on French’s and Raven’s theory (1959). From the obtained data, it was found that there were only a few linguistic features which appeared in Magnum advertisements. The power relation between the companies and the consumers could be defined easily because the utterances were clear enough. Furthermore, the simplicity of Magnum advertisements presented Magnum’s special characteristics albeit the advertisers did not vary the language style. DOI: https://doi.org/10.24071/llt.2013.160104